Seasonal Food Web Dynamics in the Antarctic Benthos of Tethys Bay (Ross Sea): Implications for Biodiversity Persistence Under Different Seasonal Sea-Ice Coverage - Caputi, Simona Sporta; Careddu, Giulio; Calizza, Edoardo; Fiorentino, Federico; Maccapan, Deborah; Rossi, Loreto; Costantini, Maria Letizia (Frontiers in Marine Science, 2020)
Determining food web architecture and its seasonal cycles is a precondition for making predictions about Antarctic marine biodiversity under varying climate change scenarios. However, few scientific data concerning Antarctic food web structure, the species playing key roles in web stability and the community responses to changes in sea-ice dynamics are available. Based on C and N stable isotope analysis, we describe Antarctic benthic food webs and the diet of species occurring in shallow waters (Tethys Bay, Ross Sea) before and after seasonal sea-ice break-up. We hypothesised that the increased availability of primary producers (sympagic algae) following sea-ice break-up affects the diet of species and thus food web architecture. Basal resources had distinct isotopic signatures that did not change after sea-ice break-up, enabling a robust description of consumer diets based on Bayesian mixing models. Sympagic algae had the highest δ13C ( -14‰) and red macroalgae the lowest ( -37‰). Consumer isotopic niches and signatures changed after sea-ice break-up, reflecting the values of sympagic algae. Differences in food web topology were also observed. The number of taxa and the number of links per taxon were higher before the thaw than after it. After sea-ice break-up, sympagic inputs allowed consumers to specialise on abundant resources at lower trophic levels. Foraging optimisation by consumers led to a simpler food web, with lower potential competition and shorter food chains. However, basal resources and Antarctic species such as the bivalve Adamussium colbecki and the sea-urchin Sterechinus neumayeri were central and highly connected both before and after the sea-ice break-up, thus playing key roles in interconnecting species and compartments in the web. Any disturbance affecting these species is expected to have cascading effects on the entire food web. The seasonal break-up of sea ice in Antarctica ensures the availability of resources that are limiting for coastal communities for the rest of the year. Identification of species playing a key role in regulating food web structure in relation to seasonal sea-ice dynamics, which are expected to change with global warming, is central to understanding how these communities will respond to climate change.